2003
DOI: 10.1038/nbt808
|View full text |Cite
|
Sign up to set email alerts
|

Widespread occurrence of antisense transcription in the human genome

Abstract: An increasing number of eukaryotic genes are being found to have naturally occurring antisense transcripts. Here we study the extent of antisense transcription in the human genome by analyzing the public databases of expressed sequences using a set of computational tools designed to identify sense-antisense transcriptional units on opposite DNA strands of the same genomic locus. The resulting data set of 2,667 sense-antisense pairs was evaluated by microarrays containing strand-specific oligonucleotide probes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
446
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 597 publications
(485 citation statements)
references
References 29 publications
37
446
0
2
Order By: Relevance
“…They are far more frequent than previously anticipated 5,48 . A recent computational survey estimated that there are ∼1,600 human SATs (∼3,200 transcriptional units) 5 . Similar results were obtained from an analysis of the mouse FANTOM2 clone set.…”
Section: Rna-directed Dna Read-outmentioning
confidence: 75%
“…They are far more frequent than previously anticipated 5,48 . A recent computational survey estimated that there are ∼1,600 human SATs (∼3,200 transcriptional units) 5 . Similar results were obtained from an analysis of the mouse FANTOM2 clone set.…”
Section: Rna-directed Dna Read-outmentioning
confidence: 75%
“…Recent progress in transcriptome analysis has revealed that a large proportion of the genome can be transcribed from both strands, producing sense and antisense transcripts (Carninci et al, 2005;Kiyosawa et al, 2003;Yelin et al, 2003). The available evidence suggests that certain classes of RNA are causally involved in not only gene regulation but also higher order chromatin structure in various organisms (Bernstein and Allis, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, public database analyses suggested the presence of approximately 1,600 sense-antisense gene pairs in the human genome (Yelin et al, 2003). These studies concluded that the occurrence of loci transcribed from both DNA strands in the mammalian genome is a common phenomenon; however, insights about their putative functional relevance are limited.…”
Section: Resultsmentioning
confidence: 99%